Daytime-only measurements underestimate CH₄ emissions from a restored bog. Issue 3 (3rd July 2018) - Dooling, Gemma P.; Chapman, Pippa J.; Baird, Andy J.; Shepherd, Matthew J.; Kohler, Tim
ABSTRACT: Accurate estimates of methane (CH4 ) fluxes from restored peatlands are needed to inform emission factor estimations and reporting. Flux measurements are usually taken during the daytime but such measurements may provide biased estimates of overall CH4 emissions if night-time fluxes differ from daytime fluxes. Diurnal variations in CH4 fluxes have been reported for a range of peatland types, but not for restored raised bogs which are important carbon stores in some countries. To help fill this knowledge gap, we investigated diurnal variations in CH4 emissions from a restored raised bog. CH4 fluxes from a restored raised bog were measured in two 24-hr field campaigns using flux chambers. Carbon dioxide (CO2 ) fluxes were also monitored, as were a suite of complementary environmental variables. Night-time CH4 fluxes were significantly greater than daytime fluxes during both campaigns, by 10.4% and 36.1%, respectively. In Campaign 1 air temperature was the best predictor of CH4 fluxes, whereas in Campaign 2 net ecosystem exchange (NEE) values were the best predictor. This study shows that diurnal variations in CH4 fluxes exist in a restored peatland and that current approaches biased to daytime measurements will underestimate CH4 emissions from restored peatlands to the atmosphere.